IMPROVING THE SYSTEM OF MONITORING OF THE ASSETS AND OPERATIONS OF THE BANKING SECTOR IN COMBATING THE CRIMINAL RECEIPT OF INCOME - Irina N. Mihailova (Статистика и экономика)
Important area for further information base work on combating money laundering is to extend the scope of financial monitoring by including in the number of organizations whose operations with monetary funds or other property subject to monitoring laundering, economic subjects, activity of which creates favorable conditions for laundering of such income. The Central place in countering unfair legalization given to the banking sector. In the scientific article is devoted to the topical issues of integration of system of financial monitoring and banking sector in the interests of solving the stated problem.